Design of a Free Fall Motion Experiment Using E18-D80NK Proximity and HC-SR04 Ultrasonic Sensors: An IoT-Based Approach - Yudha, Fauzan Syafril; Yulkifli, Yulkifli; Asrizal, Asrizal; Darvina, Yenni (Department of Physics, Universitas Negeri Padang, 2024)
Electronics plays an important role in science, especially in the advancement of school laboratory equipment which is one of the pillars of education. Many laboratories equipment currently still use manual methods. This research aims to develop an IoT-based free fall motion measurement system that displays measurement results automatically. This system uses E18-D0NK proximity sensor and HC-SR04 ultrasonic based on ESP32. This research focuses on engineering a free fall motion measurement tool with the method of dropping objects. Data collection is done through direct and indirect approaches. Direct measurement involves reading the value on the smartphone screen, while indirect measurement is used to evaluate the level of accuracy and precision of the digital measurement system compared to conventional methods. The data obtained was statistically analyzed and represented in graphical form to provide a comprehensive understanding of the performance of the developed system. From the data analysis, there are two important findings. First, the measurement system includes an E18-D0NK proximity sensor for starting and stopping the movement of objects and an HC-SR04 ultrasonic sensor for measuring height, all housed in a toolbox. Second, the system shows excellent average accuracy and average precision.